Mengoptimalkan Keuntungan UMKM melalui Pengelolaan HPP, Kemasan Produk, Laba Rugi, dan Margin Keuntungan - PUTRI DISTRIANI; Novia Susanti (PPPM Institut Teknologi Pagar Alam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in determining appropriate selling prices due to limited understanding of comprehensive cost of goods manufactured (COGM) calculations, packaging costs, profit and loss analysis, and profit margin determination. The community service training program entitled optimizing MSME Profits through the management of cost of goods manufactured (COGM), product packaging, profit and loss, and profit margins aimed to enhance the knowledge and skills of MSME owners in managing production costs and developing pricing strategies to improve business competitiveness. The training methods included lectures, interactive discussions, case studies, and hands-on exercises in calculating COGM, packaging costs, profit and loss, and profit margins based on the participants' products. Program evaluation was conducted through observations of participant engagement and their ability to complete case study exercises. The results indicated a significant improvement in participants' understanding of production cost components, the importance of selecting appropriate packaging based on product characteristics and target markets, and the ability to determine selling prices based on COGM and desired profit margins. In addition, participants demonstrated improved competence in analyzing profit and loss statements as a basis for business decision-making. This training is expected to assist MSMEs in implementing better financial management practices, improving cost efficiency, setting rational selling prices, and strengthening business sustainability.